The system of supply of siliceous rocks between the Drava, Sava and Danube rivers during the Starčevo culture - Šošić Klindžić, Rajna (2011)
This paper analyses the production processes of chipped stone artefacts from ten Star- ≠evo culture sites in the area between the rivers Sava, Drava and Danube. The aim was to compare the results of analysis of assemblages from individual settlements to reconstruct the existence and extent of relationships between settlements and their inhabitants. The results showed that in the area between Sava and Drava during the early Neolithic period, a system for acquiring and processing raw materials and the production and exchange of stone tools among the settlements developed. The Star≠evo culture population was familiar with the environment and resources, and had developed a system of procurement and distribution of raw material and intermediate goods.
Projekt MZOS
ENG